2009
DOI: 10.1007/bf03218674
|View full text |Cite
|
Sign up to set email alerts
|

Alginate nanohydrogels prepared by emulsification-diffusion method

Abstract: This study reports the preparation and characterization of nanohydrogels by using sodium alginate as a model material. Alginate nanohydrogels (ANH) were prepared by emulsification-diffusion method in a w/o system with 1,2-diacyl-sn-glycero-3-phosphocholin as the lipophilic surfactant. The effects of the alginate to surfactant ratio and the remaining water contents on the mean particle size and swellability of ANHs were investigated in terms of the concentration, agitation speed, and agitation time. The feasibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…In the case of the ANH, to ensure the sufficient diffusion of water and the solidification of nanoparticles, the emulsion was left at room temperature for 3 days. 28 On the other hand, in the case of the BMP-2@ANH, proteins may be readily diffused out of the nanohydrogels for 3 days. To minimize the loss of BMP-2, the emulsion was left only for 10 min, which led to insufficient diffusion of water, aggregation, and accordingly, larger particles size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the ANH, to ensure the sufficient diffusion of water and the solidification of nanoparticles, the emulsion was left at room temperature for 3 days. 28 On the other hand, in the case of the BMP-2@ANH, proteins may be readily diffused out of the nanohydrogels for 3 days. To minimize the loss of BMP-2, the emulsion was left only for 10 min, which led to insufficient diffusion of water, aggregation, and accordingly, larger particles size.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of BMP-2@ANH were based on the modified emulsificationdiffusion method described in the previous paper. 28 Briefly, 0.1 g of sodium alginate (Junsei Chemical, Japan) and 4×10 -6 g of BMP-2 (Peprotech, USA) were dissolved in 20 mL of water. This aqueous solution was saturated with equivalent amount of chloroform (Duksan Pure Chemical, Korea) with 1,2-diacyl-sn-glycero-3-phosphocholin (Cholin II) (Sigma, USA) to reach the state of thermodynamic equilibrium.…”
Section: Methodsmentioning
confidence: 99%
“…Chloroform (water solubility 0.809 g/100 mL at 20 C, dielectric constant 4.8) was used instead to dissolve the NIR dye and PCL yielded a blue transparent mixture. 26 Firstly, the partially watersoluble chloroform was saturated with DI water ensuring an initial thermodynamic equilibrium of both liquids which can avoid mass-transfer during the process. 27 The reaction began aer the addition of surfactant dissolved in chloroformsaturated water into water-saturated chloroform containing a mixture of PCL and NIR dye under ultrasonic treatment.…”
Section: Preparation Of Pcl-pf8nt2/6 Nanoparticlesmentioning
confidence: 99%
“…These results are in alignment with those of Lee et al, who reported that the sizes of alginate nanohydrogels obtained by TEM observation were much smaller. 40 XRD. The XRD patterns of nanohydrogels prepared with different retrogradation times are shown in Figure 5.…”
Section: Particle Size Distribution Of Starch Nanohydrogelsmentioning
confidence: 99%